2017
DOI: 10.1371/journal.pone.0177546
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and trust of the FDA and CDC: Results from a national sample of US adults and adolescents

Abstract: Trust in government agencies plays a key role in advancing these organizations' agendas, influencing behaviors, and effectively implementing policies. However, few studies have examined the extent to which individuals are aware of and trust the leading United States agencies devoted to protecting the public’s health. Using two national samples of adolescents (N = 1,125) and adults (N = 5,014), we examined demographic factors, with a focus on vulnerable groups, as correlates of awareness of and trust in the Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 27 publications
0
58
1
Order By: Relevance
“…Such differences are not surprising. Previous research has demonstrated lower levels of trust among smokers in sources of health information [ 37 ] and in government agencies [ 5 ]. In addition, research on information processing shows that when a message is threatening to one’s existing attitude, those who believe that the message is relevant to them are more likely to generate critical judgments regarding the message’s content, quality, and credibility than individuals for whom the message is less relevant [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such differences are not surprising. Previous research has demonstrated lower levels of trust among smokers in sources of health information [ 37 ] and in government agencies [ 5 ]. In addition, research on information processing shows that when a message is threatening to one’s existing attitude, those who believe that the message is relevant to them are more likely to generate critical judgments regarding the message’s content, quality, and credibility than individuals for whom the message is less relevant [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions of FDA’s credibility as a tobacco regulator (i.e., its expertise, trustworthiness, and accountability in this role) may also determine receptivity to, and persuasion by, FDA communications about the harms of tobacco products [ 4 ]. Research in the United States (US), however, shows moderate levels of trust in government agencies, including those that were tasked to implement tobacco control measures [ 5 , 6 ]. One study found that federal agencies, such as FDA, the Centers for Disease Control (CDC), and the National Institutes of Health (NIH) emerged third (42%) in ratings of trust in online health information resources after personal doctor (59%), and medical universities (48%) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…National polling data shows that despite having high levels of trust in federal health agencies overall, trust levels have recently declined, and trust in pharmaceutical companies is at an all-time low (Harris Poll, 2015; Gallup Poll, 2016). A recent study confirmed 65% of American adults trust the CDC and 63% trust the FDA (Kowitt et al, 2017). Trust in the role these institutions play in the vaccine process is less studied.…”
Section: Introductionmentioning
confidence: 95%
“…It is possible that adults perceive the source agencies in similar ways or that adults in the U.S. may assume that a tobacco warning is coming from a government health agency, even if this is not explicitly stated. Recently published data from the same dataset found that trust in CDC and FDA is 64.6% and 62.5%, respectively [ 30 ]. Previous evidence indicates for-profit sources, like the tobacco industry, can result in significantly lower believability by source [ 18 , 19 , 31 ].…”
Section: Discussionmentioning
confidence: 99%